Breathe right nasal strips: Not for most athletes - Hatfield, F. (Sportscience)
Summary: Breathe right nasal strips have little or no effect on the amount of air that passes through your lungs, or on the amount of oxygen you can extract from the air during exercise. Performance of and recovery from maximal endurance exercise by normal healthy adults under normal laboratory conditions also appears to be unaffected. A study showing that nasal dilation can reduce heating of the brain during exercise needs to be repeated with Breathe Right strips while athletic performance is monitored under various conditions. My recommendation: the strips are silly for most athletes, but they may work when high body temperature reduces performance.